If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 17 = 11x + -67 Reorder the terms: 17 + 4x = 11x + -67 Reorder the terms: 17 + 4x = -67 + 11x Solving 17 + 4x = -67 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 17 + 4x + -11x = -67 + 11x + -11x Combine like terms: 4x + -11x = -7x 17 + -7x = -67 + 11x + -11x Combine like terms: 11x + -11x = 0 17 + -7x = -67 + 0 17 + -7x = -67 Add '-17' to each side of the equation. 17 + -17 + -7x = -67 + -17 Combine like terms: 17 + -17 = 0 0 + -7x = -67 + -17 -7x = -67 + -17 Combine like terms: -67 + -17 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 6x+9=-39-10x | | 6(a-2)-bc= | | 12m+8-5m+2+m=6(m+1) | | 4y+3=2y+5 | | 12x=36-6x | | 5x-11=34 | | -22-2x=7x+24 | | 10x=7x+15 | | -30=3(m-17) | | x^2-5x-18=0 | | 4x-3=10-7x | | 147-6x=3x+12 | | 108-7x=11x+16 | | k-6x-m=0 | | -5-6x=7-8x | | -69-9x=8x+16 | | 2x-54=x+22 | | 6x+11=-117-10x | | 2(a+6b)-3= | | 6x+14=94-4x | | 7x-12=(-36x) | | 80-3x=3x+14 | | 7p-(2p-27)=2 | | -124-8x=8x+20 | | 5x=-2x+14 | | 7x-12=-36x | | 6x+7=83-5x | | 13t-7710t=2 | | 4x^2-13x+29=7x+8 | | 5X-2s= | | 2x+26=11x-73 | | 6x^2-11x-35=0 |